Frequency Characteristics of Layered Medium Consisted of Biperiodic Strip Arrays - Litvinenko, L. M.; Prosvirnin, S. L.; Tyrnov, D. O. (Видавничий дім «Академперіодика», 2013)
Frequency Characteristics of Layered Medium Consisted of Biperiodic Strip Arrays